2018
DOI: 10.3897/subtbiol.26.26643
|View full text |Cite
|
Sign up to set email alerts
|

A new cave locality for Astyanax cavefish in Sierra de El Abra, Mexico

Abstract: The characiform fish Astyanaxmexicanus comes in two forms, a surface-dwelling morph which lives in the rivers of North and Central America and a blind, depigmented cave-dwelling morph which inhabits caves in Mexico. In recent years, this species has arguably become among the most influential model system for the study of evolutionary development and genomics in cave biology. While recent articles have analysed in great detail Astyanax genetics, development, physiology, phylogeny and behaviour, there have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…"Chiquitita" cave should not be confused with "Chica" cave. Chiquitita is the most recently discovered cave with a cavefish population (Espinasa et al 2018), found south of Chica cave, in the town of El Pujal, at the southernmost tip of Sierra de El Abra.…”
Section: Methodsmentioning
confidence: 99%
“…"Chiquitita" cave should not be confused with "Chica" cave. Chiquitita is the most recently discovered cave with a cavefish population (Espinasa et al 2018), found south of Chica cave, in the town of El Pujal, at the southernmost tip of Sierra de El Abra.…”
Section: Methodsmentioning
confidence: 99%
“…We included one cavefish population (Pachón) from the Sierra de El Abra, a mountain range running north to south along the eastern margin of the Sierra Madre Oriental, a karstic region in northeastern Mexico ( Elliott, 2016 ). El Abra is considered as one of the highest flowing karst springs worldwide ( Gary & Sharp, 2006 ) and the presence of A. mexicanus cavefish populations have been reported in at least 30 caves in the region ( Elliott, 2016 ; Espinasa et al, 2018 ). Additionally, we included two surface populations located at the vicinity of El Abra, between the Sierras Las Crucitas and Sierra de la Colmena (San Luis Potosí, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Cueva Chiquitita is inhabited by surface, troglomorphic, and hybrid fish. It is also likely that there is a continuous underwater passage between Cueva Chiquitita and one of the most cited Astyanax cave localities, Cueva Chica [6,8]. Subsurface hydrologic connections allow for both troglomorphic and surface fish to migrate between El Abra cave localities.…”
Section: Introductionmentioning
confidence: 99%
“…This is a low-lying area that has little potential for deep caves. Most caves were explored in the 1970's, and cavers at that time may have put less effort into describing shallow caves that would nevertheless be of biological interest [6,8]. Supporting evidence for the possibility of new discoveries was the aforementioned recent discovery of Cueva Chiquitita in this area [8].…”
Section: Introductionmentioning
confidence: 99%